2010
DOI: 10.1161/strokeaha.109.574004
|View full text |Cite
|
Sign up to set email alerts
|

The Akt-Endothelial Nitric Oxide Synthase Pathway in Lipopolysaccharide Preconditioning-Induced Hypoxic-Ischemic Tolerance in the Neonatal Rat Brain

Abstract: Background and Purpose-Low-dose lipopolysaccharide (LPS) preconditioning provides neonatal rats long-term neuroprotection against hypoxic ischemia (HI). Upregulating endothelial nitric oxide synthase (eNOS) protects against cerebral ischemia; however, whether eNOS is required for LPS preconditioning-induced protection in neonatal rats is unknown. We hypothesized that Akt activation, which upregulates eNOS in neurons and endothelial cells, is required for LPS preconditioning-induced tolerance against HI in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
(42 reference statements)
4
25
0
2
Order By: Relevance
“…In future studies, it will be important to investigate whether continued or sustained exposure to low-dose LPS during induction of HI has any further effect on the evolution of injury. The present findings of delayed protection support the view that preconditioning or cross-tolerance induces a transient window of protection which is dependent on gene induction and de novo protein synthesis, consistent with in vitro [69,70] and in vivo [71,72,73,74,75] neonatal and adult rat models of ischemia.…”
Section: Discussionsupporting
confidence: 88%
“…In future studies, it will be important to investigate whether continued or sustained exposure to low-dose LPS during induction of HI has any further effect on the evolution of injury. The present findings of delayed protection support the view that preconditioning or cross-tolerance induces a transient window of protection which is dependent on gene induction and de novo protein synthesis, consistent with in vitro [69,70] and in vivo [71,72,73,74,75] neonatal and adult rat models of ischemia.…”
Section: Discussionsupporting
confidence: 88%
“…It was shown that systemic LPS-or ischemiainduced preconditioning causes neuroprotection as a long term outcome through mechanisms involving several different pathways including COX-2, nitric-oxide synthase, and reactive oxygen species (47)(48)(49). Interestingly, also in the hypoxic slice culture model by Kim et al (47) COX-2 activity was crucial for preconditioning-induced neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…LPS preconditioning involves injecting low doses of this potent bacterial endotoxin in rodents before the final insult (hypoxia ischemia, MCAO), which later imparts IT in the brain [75,132]. Yet, another mode of CPC involves estrogen preconditioning [36].…”
Section: Preconditioning Agentsmentioning
confidence: 99%